4z+5=6z+7

Simple and best practice solution for 4z+5=6z+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4z+5=6z+7 equation:


Simplifying
4z + 5 = 6z + 7

Reorder the terms:
5 + 4z = 6z + 7

Reorder the terms:
5 + 4z = 7 + 6z

Solving
5 + 4z = 7 + 6z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-6z' to each side of the equation.
5 + 4z + -6z = 7 + 6z + -6z

Combine like terms: 4z + -6z = -2z
5 + -2z = 7 + 6z + -6z

Combine like terms: 6z + -6z = 0
5 + -2z = 7 + 0
5 + -2z = 7

Add '-5' to each side of the equation.
5 + -5 + -2z = 7 + -5

Combine like terms: 5 + -5 = 0
0 + -2z = 7 + -5
-2z = 7 + -5

Combine like terms: 7 + -5 = 2
-2z = 2

Divide each side by '-2'.
z = -1

Simplifying
z = -1

See similar equations:

| -3[w+5]+5w=2[w-6] | | 8+5x=-27 | | -9f+2+8-5f= | | 6-s=18 | | [(2x+1)-5(x-4)]+4=10(x+3) | | 5h-(8+7h)= | | 2(4e)=40 | | 1=3(k+8) | | 5-7f+8f-3= | | 13=z+5 | | 6w+5=29 | | -9-1.1x=6.8 | | x+4x-21= | | (4x-23)+(2x+17)=180 | | -6x-2x+13=-11 | | 3[x+2]+2x=7[x-1]+9 | | 5+0.1Q=20-0.2Q | | 2(4e)=35 | | 2=11-20 | | 3n^2-6n+8=0 | | 2y=37 | | 8y-6y-3=17 | | 6-18p= | | -5+8s-7+3s= | | 48=5w+8 | | 15x^2-2=0 | | -2(x+4)+8x=-14 | | 2z-6=10z+6 | | 2=-2(n-7) | | (3(42.5)+x+10)+(42.5+x)=180 | | 6y^2-2y-3=0 | | 5h+9+7h= |

Equations solver categories